Electrocatalytic reduction of alkyl iodides in tetrahydrofuran at silver electrodes - Paddon, C; Bhatti, F; Donohoe, T; Compton, R (2007)
Recent interest in the electrocatalytic activity of silver towards the reduction of alkyl iodides haş led us to investigate whether the effect is observed in tetrahydrofuran (THF) at room temperature. Using platinum electrodes in THF for the reduction of alkyl halides at 298 K has been hampered by the solvent window, which 'obscures' the voltammetric signals of interest. In order to overcome these problems, voltammetry has been performed at low temperature and was shown to extend the voltammetric window, leading to accurate electrochemical analyses and even novel changes in mechanism(s) of the reactive species following electron-transfer (ET). Herein, it is shown that for a primary and tertiary alkyl iodide in THF, electroreduction at silver leads to a significant shift in the reduction potential to more positive values compared to platinum. In addition, following reduction, a characteristic series of oxidation peaks are observed and are shown to be due to the specific activity of iodide ions towards silver following reductive cleavage of the parent alkyl iodide. This characteristic feature is not observed with other halide ions: bromide and chloride. Preparative electrolyses at controlled-potential have suggested that the reduction of the above alkyl iodides is a one-electron concerted process. The 'free' iodide ions act as a monitor of reaction progression, and the carbon-centred radical either dimerises and/or abstracts a hydrogen atom from the electrolyte/solvent; 1-iodoadamantane giving percentage yields of 58% adamantane and 39% 1,1'-biadamantane, the primary alkyl iodide, prepared in-house, giving 67% R-H and 25% R-R. Copyright © 2007 John Wiley and Sons, Ltd.